Jonas. Rockin' the house. Vol. 1 [videorecording (DVD)] - Jonas, Kevin, 1987-; Jonas, Joe, 1989-; Jonas, Nick; Staub, Chelsea (Walt Disney Studios Home Entertainment, 2009)
Kevin, Nick, and Joe are international superstars trying to live normal lives as teens. When Nick writes a love song for a girl he likes, his brothers try to convince him that he's moving too fast; the boys plan an awesome surprise for their mom's birthday; The brothers fall head over heels for the pizza girl, Maria, and after racking up a huge bill they are banned from ordering again; Carl, a childhood friend, visits them and manipulates their popularity to his advantage.